Bartsocas-Papas syndrome: The first case report of severe autosomal recessive form from Indonesia. (February 2021) - Josh, Fonny; Soekamto, Tomie Hermawan; Marzoeki, Djohansjah; Faruk, Muhammad
Highlights: Bartsocas-Papas syndrome (BPS) is a very rare congenital syndrome. Almost all cases were reported in dead intrauterine pregnancies. We repaired the ectropion and grafted skin to the eyelids to prevent further damage. Tissue expanders and reconstruction were used to close labia and nasal defects. We report a BPS case that was handled optimally in a multidisciplinary manner. Abstract: Introduction: Bartsocas-Papas syndrome (BPS) is an autosomal recessive form of Popliteal Pterygium syndrome (PPS). It is a very rare disease characterized by congenital craniofacial anomalies, popliteal webbing, and genitourinary and musculoskeletal anomalies. Almost all of the cases were reported in dead intrauterine pregnancies. Presentation of case: We present a 10-month-old boy with bilateral complete cleft lip and palate, abnormal scalp hair, an absence of both upper eyelids, choanal atresia, syndactyly of the third and fourth fingers of the right hand, agenesis fingers on the left hand, bilateral popliteal pterygia, bilateral talipes equinovarus, agenesis of the toes of both lower extremities, intercrural webbing, an absence of testis, and scrotal anomaly. Multistage surgical correction was performed for the multiple congenital malformations. Conclusion: We report the first case of BPS from Indonesia. Gradual management should be performed according to the patient's age and available facilities.